2019
DOI: 10.1088/1674-1056/28/1/014201
|View full text |Cite
|
Sign up to set email alerts
|

Propagation characteristics of oblique incidence terahertz wave through non-uniform plasma

Abstract: The propagation characteristics of oblique incidence terahertz (THz) waves through non-uniform plasma are investigated by the shift-operator finite-difference time-domain (SO-FDTD) method combined with the phase matching condition. The electron density distribution of the non-uniform plasma is assumed to be in a Gaussian profile. Validation of the present method is performed by comparing the results with those obtained by an analytical method for a homogeneous plasma slab. Then the effects of parameters of THz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The reliability of the calculation results in this work can be verified with the following example. About the oblique incidence of electromagnetic waves in plasma, Chen et al have published related calculation results in their papers [16,17]. The comparison and verification of the calculation results show the reliability of the calculation.…”
Section: H X Y T Y E X Y T Tmentioning
confidence: 96%
“…The reliability of the calculation results in this work can be verified with the following example. About the oblique incidence of electromagnetic waves in plasma, Chen et al have published related calculation results in their papers [16,17]. The comparison and verification of the calculation results show the reliability of the calculation.…”
Section: H X Y T Y E X Y T Tmentioning
confidence: 96%
“…Dong et al [10] investigated the transmission characteristics of terahertz waves in plasma sheaths with different flight speeds and different incidence angles by using the finite difference method of the time domain (FDTD). Chen et al [11] investigated the transmission characteristics of electromagnetic waves in plasma sheaths at different angles of incidence by using the improved scattering matrix method (ISMM). Hao Li theoretically analyzed and calculated the transmission behavior of terahertz waves at different electron densities, magnetic field distributions, and collision frequencies using the scattering matrix method (SMM) [12].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely used to analyze electromagnetic wave transmission characteristics in plasma, such as through using the Wentzel-Kramer-Brillouin (WKB) method, scattering matrix method (SMM), finite-difference time-domain (FDTD) method. [14][15][16][17][18][19][20][21][22][23][24][25] Yu et al used the WKB method to study the transmission characteristics of terahertz waves in magnetized plasmas with different electron density distributions. [26] Numerical simulation results demonstrated that the plasma density, plasma slab thickness, plasma density models, and collision frequency significantly influence the attenuation and transmittance of terahertz waves.…”
Section: Introductionmentioning
confidence: 99%